Advances in Taxation - Hasseldine, John (Advances in taxation, 2024)
In Volume 31 of Advances in Taxation, the editor John Hasseldine includes studies from expert contributors to explore topics such as: firms' domestic and foreign effective tax rates; tax avoidance; and tax compliance. In addition, one study reviews prior literature on tax increment financing, an economic development tool frequently used by U.S. local governments. Reporting peer-reviewed research contributions from the U.S. and Canada, this volume is essential reading for those looking to keep abreast of the most recent research, including empirical studies using a variety of research methods from different institutional settings and contexts.